2023
DOI: 10.1146/annurev-pharmtox-051921-121923
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-Activated Protein Kinase Phosphatases: No Longer Undruggable?

Abstract: Phosphatases and kinases maintain an equilibrium of dephosphorylated and phosphorylated proteins, respectively, that are required for critical cellular functions. Imbalance in this equilibrium or irregularity in their function causes unfavorable cellular effects that have been implicated in the development of numerous diseases. Protein tyrosine phosphatases (PTPs) catalyze the dephosphorylation of protein substrates on tyrosine residues, and their involvement in cell signaling and diseases such as cancer and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…Until now, the role of DUSP8 in the progression of cancer has been largely neglected. By using a phosphokinase assay, we were able to identify potential new substrates GSK-3α/β, GSK-3β, Src, STAT5a/b, WNK1, PRAS40, RSK1/2, β-catenin, c-Jun and HSP60 known as drivers of cancer, whose relevant residues could be dephosphorylated by DUSP8 in addition to the reported DUSP8 relevant residues of JNK and p38 [ 21 , 22 ]. Our in silico analysis of genes associated with JNK signaling revealed that OS is decreased in lung cancer when downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the role of DUSP8 in the progression of cancer has been largely neglected. By using a phosphokinase assay, we were able to identify potential new substrates GSK-3α/β, GSK-3β, Src, STAT5a/b, WNK1, PRAS40, RSK1/2, β-catenin, c-Jun and HSP60 known as drivers of cancer, whose relevant residues could be dephosphorylated by DUSP8 in addition to the reported DUSP8 relevant residues of JNK and p38 [ 21 , 22 ]. Our in silico analysis of genes associated with JNK signaling revealed that OS is decreased in lung cancer when downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies will need to address the question whether NMA1982 is indeed crucial for N. meningitidis survival and virulence, and thus may validate NMA1982 as a novel therapeutic target for the treatment of meningococcal diseases. Human PTPs have become attractive drug targets for many serious conditions, most notably cancer [49][50][51] . Compared to human PTPs, the shorter P-loop in NMA1982 results in a unique active site conformation, which may allow for the development of small molecule inhibitors with selectivity for the N. meningitidis protein.…”
Section: Discussionmentioning
confidence: 99%
“…While activation of the signaling cascade is corroborated by phosphorylation, dephosphorylation catalyzed by a phosphatase is needed to terminate the signaling to avoid excessive proliferation [ 129 ]. Most protein phosphatases are either specific to phospho-Ser/-Thr, designated as PPT, or phospho-Tyr, designated as PTP, while phosphatase and tensin homologs (PTEN) are specific to phosphatidylinositides [ 90 , 126 , 130 ]. The reaction mechanisms for PPT and PTP during dephosphorylation are completely different, while there is a similarity between PTP and PTEN in that they both employ Cys as the catalytic amino acid.…”
Section: Cellular Responses To 1 Omentioning
confidence: 99%